Advancements and Challenges in Dental Forensics for Disaster Victim Identification: A Comprehensive Review - Ningombam Jyostna (International Journal of Medical Toxicology and Legal Medicine, 2024)
Mass disasters whether manmade or natural have severe consequences. One of the most challenging aspects is the identification of the victim. Conventional and visual method identification is very difficult, so forensic methods become essential, and dental forensics plays a pivotal role in the identification of the victims. Forensic odontologists actively participate in every stage of the identification process, adapting to emerging challenges by incorporating modern scientific methods into their approaches to identification. The success of the identification process hinges entirely on the presence of well-preserved dental remains following the disaster and the accessibility of corresponding dental records. To achieve a scientifically supported positive identification, capable of withstanding international legal scrutiny, a meticulously organized and pre-planned management of the mass disaster victim identification process is necessary. This should adhere to the guidelines set forth by the international Interpol Disaster Victim Identification (DVI) Standing Committee. This paper describes the utilization of dental evidence for identification purposes exploring existing and prospective techniques that could enhance the efficiency of the identification process and outlines recent advances.